Comparison of analgesic efficacy of continuous transversus abdominis plane (TAP) block with continuous epidural analgesia in renal transplant recipients - Hemant Ojha; Ishwar Bhukal; Aveek Jayant; Sarbpreet Singh; Reshma Mulla; Pulak Priyadarshi Padhi (Saudi Journal of Anaesthesia)
Background: Transversus abdominis plane (TAP) block has been shown to be an effective analgesic modality for various abdominal surgeries. In this study, a direct comparison between continuous TAP block with continuous epidural block was made in kidney transplant recipients. Methods: A total of 62 participants were randomly allotted to receive either continuous epidural or continuous TAP block. In the epidural group, infusion of 0.25% ropivacaine at a rate of 4–10 mL per hour depending on patient characteristics and block level as assessed clinically. In the TAP block group, after an ultrasound-guided posterior approach TAP block, a bolus of 0.25% ropivacaine (20 mL) was deposited in the plane, followed by a continuous infusion of 0.25 ropivacaine. In both groups, the infusion was continued for 24 h postoperatively. Rescue analgesia was provided in the form of patient-controlled fentanyl intravenously. Numerical pain rating score (0–100) was recorded at each of the study points (0, 1, 2, 6, 12, and 24 postoperatively). Results: Demographic data and baseline investigations were not significantly different between the groups. No significant difference was found between the median numerical pain rating scale (NRS) scores at rest and on coughing at all study points (P > 0.05). The mean consumption of fentanyl in 24 h postoperatively was similar in group E (685.48 ± 76.86) and group T (695.16 ± 78.37). Similarly, no significant difference was noted in the hemodynamic parameters and patient satisfaction (P > 0.05). Conclusions: Continuous TAP block is non-inferior to epidural technique for postoperative analgesia in patients undergoing renal transplant recipients.